(untitled) (Journal of Economic Research & Business Administration, 2015)
The article is devoted to the study of theinternational credit’simpacton the economyof Kazakhstan. It is shown thatinternational creditstimulateseconomic development,resulting in the expansionof international integrationthat promotesforeign investment inKazakhstan.It allows Kazakhstanto receive financial andtechnical resourcesfor social andeconomic development of the country.In this articlewas held a comparative analysis of dataon internationalcredits which are invested in theeconomy of Kazakhstan. There are materialsof the official websitesof internationalbanksfor developmentin this work.Nowadays the Republic ofKazakhstanisa member state ofthe sevenwell-known internationalbanks for development(IBD) such as EBRD, ADB, EABR, EIB, IEF, IBRD and ISDB. It strengthens theinterstate positionofour country